2018
DOI: 10.4236/fns.2018.93014
|View full text |Cite
|
Sign up to set email alerts
|

Single Oral Administration of Anthocyanin Rescues Smoking-Induced Endothelial Dysfunction in Young Smokers but Facilitates Oxidative Stress in Non-Smokers

Abstract: Objectives: Smoking causes endothelial dysfunction, but it still remains unclear whether oral administration of anthocyanin brings benefits to endothelial function and redox states in young healthy smokers. We tested the hypothesis that supplement anthocyanin may rescue endothelial dysfunction and redox states in young healthy smokers. Methods: Young healthy male non-smoker (n = 8) and smokers (n = 14) were enrolled to measure the derivatives of reactive oxygen metabolites (d-ROMs) and biological antioxidant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…However, in this study, complementing vitamin E tended to ameliorate endothelial functions in healthy nonsmokers as well as smokers, thereby blunting the beneficial effect of anthocyanin. It is important to avoid excess intake of polyphenol in healthy nonsmokers because excess polyphenol overtaxes their bodies [35]. In the present study, we showed that smoking impaired endothelial function acutely in healthy young persons, indicating the importance of prohibiting smoking in young individuals.…”
Section: Discussionsupporting
confidence: 57%
“…However, in this study, complementing vitamin E tended to ameliorate endothelial functions in healthy nonsmokers as well as smokers, thereby blunting the beneficial effect of anthocyanin. It is important to avoid excess intake of polyphenol in healthy nonsmokers because excess polyphenol overtaxes their bodies [35]. In the present study, we showed that smoking impaired endothelial function acutely in healthy young persons, indicating the importance of prohibiting smoking in young individuals.…”
Section: Discussionsupporting
confidence: 57%
“…The BCE powder, Active Cassis, a dietary supplement, was purchased from Just The Berries Limited, Palmerston North, New Zealand. One hundred grams of the powder consists of 35.0 g of total anthocyanins, 13.6 mg of carbohydrates, 0.5 g of fats, and 0.1 g of proteins, and yields 1650 kilojoules (394 Kcal) of energy [ 38 ]. A total of 230 mg BCE was filled in opaque hard capsules.…”
Section: Methodsmentioning
confidence: 99%